Determinants of exports of plastic industry products and their implications for trade balance and employment: Case studies of several ASEAN countries - Damayanti, Dian; Subianto, Prabowo; Apon, Moh.; Toharudin, Toni; Susilastuti, Darwati; Gultom, Juni; Ratnasih, Cicih; Bernanthos, Bambang; Royani, Esti (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the determinants of the export of plastic industry products and their implications for the trade balance and labor absorption in several ASEAN countries during the period 2013–2022. The background of this research is based on the importance of the plastic industry sector in supporting international trade performance and its potential contribution to regional economic growth. The method used was panel data regression analysis with a fixed effect model (Fixed Effect Model) using the Ordinary Least Squares (OLS) approach and data processing through EViews 13 software. The results show that logistics infrastructure and the amount of plastic production have a positive and significant effect on exports, while inflation has a negative and significant effect. In contrast, the exchange rate and foreign direct investment (FDI) showed no significant influence. These findings emphasize the importance of strengthening logistics infrastructure and macroeconomic stability as the key to increasing export competitiveness. The conclusion of this study is that the export of plastic products plays an important role in boosting the trade balance of ASEAN countries, but it is not optimal in creating significant jobs.